Contact lenses as drug controlled release systems: a narrative review - Filipe, Helena Prior (2017)
Topically applied therapy is the most common way to treat ocular diseases, however given the anatomical and physiological constraints of the eye, frequent dosing is required with possible repercussions in terms of patient compliance. Beyond refractive error correction, contact lenses (CLs) have, in the last few decades emerged as a potential ophthalmic drug controlled release system (DCRS). Extensive research is underway to understand how to best modify CLs to increase residence time and bioavailability of drugs within therapeutic levels on the ocular surface.These devices may simultaneously correct ametropia and have a role in managing ophthalmic disorders that can hinder CL wear such as dry eye, glaucoma, ocular allergy and cornea infection and injury. In this narrative review the authors explain how the ocular surface structures determine drug diffusion in the eye and summarize the strategies to enhance drug residence time and bioavailability. They synthesize findings and clinical applications of drug soaked CLs as DCRS combined with delivery diffusion barriers, incorporation of functional monomers, ion related controlled release, molecular imprinting, nanoparticles and layering. The authors draw conclusions about the impact of these novel ophthalmic agents delivery systems in improving drug transport in the target tissue and patient compliance, in reducing systemic absorption and undesired side effects, and discuss future perspectives.